Pediatric Bronchospasm During General Anesthesia - Christina Spofford; Paul Miska (Association of American Medical Colleges, 2015)
Abstract This simulation is designed for junior anesthesia trainees to experience the physiological repercussions of a pediatric patient with significant bronchospasm during a general anesthetic. The simulation functions as a tool for training, evaluating, and reinforcing material learned in the classroom and operating room. Trainees with different backgrounds and experiences can utilize this simulation module for further learning about the complications of pediatric anesthesia. This supplemental simulation-based learning module allows for training that reduces patient risk by giving learners a chance to become aware of the condition before treating a real patient, is observable and repeatable, and allows for the freedom to make mistakes and reflect upon different actions in the future. The module includes an instructor's guide, the simulation scenarios, a technical guide, a debriefing document, and an evaluation form. The scenario is used for practice, evaluation, and self-identification of weaknesses in the learner's knowledge base in regard to perioperative management of the pediatric patient. Several anesthesia residents participated in this scenario, with frequent revisions and updates made based on feedback. In our simulation center, we expect to run these scenarios about 15 times annually for our CA-1 class, although in other institutions where pediatric anesthesia rotations are done later in training, the scenarios may be used for more senior trainees.